A Novel Laser Tool for High‐Volume Sample Preparation. Issue 1 (January 2015) - Höche, Thomas; Krause, Michael; Ebert, Martin; Wagner, Uwe; Gebhardt, Mandy
Abstract Over the past fifty years, lasers have perpetuated to find new, often groundbreaking applications in science and technology. The most important features of lasers are that photons are inherently free of elemental contamination, extremely high energy densities can be focused in very small areas and the laser beam can be precisely positioned using deflection mirrors. By reducing pulse lengths from a few nanoseconds down to the picosecond or femtosecond range, materials ablation is becoming increasingly "athermal", i. e., structure damage by local heating is reduced to well below a few microns. In view of these outstanding characteristics of lasers as tools for micromachining, it is very surprising that sample preparation for microstructure diagnostics so far hasn't made use of laser technology.